Peningkatan Pemahaman Teknik Pemanduan Wisata Pada Siswa SMK Negeri 2 Semarang - Wibowo, Muchammad Satrio; Paninggiran, Herman Novry Kristiansen; Jannah, Desika Nur; Imanina, Almas Nabili; Nurfitrianti, Riza Dewi; Aminati, Evita (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
A tour guide is someone who provides information related to the destinations visited. A guide must continuously improve their knowledge, skills, and attitudes in carrying out their duties. Producing highly dedicated guides can be done through stages. One way is through Vocational High Schools (SMK) with a major in tourism. SMK Negeri 2 Semarang is one of the schools that has a Tourism Service Business Expertise Program (ULP). One of its concentrations is tour guiding. A program is needed to improve students' understanding of tour guiding techniques. This community service activity is one option for providing training for students. The goal is to improve students' understanding and skills in tour guiding techniques. The method used is a lecture by the community service team and direct practice by participants. The level of understanding was measured using a Likert scale calculation through a pre-test and post-test. The pre-test results showed a percentage index value of 77.71% - 83.43%, and the post-test ranged from 88.57% - 90.29%. There was an increase in the participants' understanding scores. Improving understanding is crucial for mastering a material. Understanding the material is essential in the learning process so that participants can practice correctly. This will ensure the desired results and reduce errors.